PREPARATION AND EVALUATION OF QUETIAPINE FUMARATE MICROEMULSIONS: A NOVEL DELIVERY SYSTEM - Parvathi, M.; Prathyusha, A.; R.S.V.Kiran; Raveendra reddy, J. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In the present study, the main objective is to improve solubility and bioavailability of Quetiapine fumarate by formulation into micro emulsion. Method: The Quetiapine fumarate micro emulsion was formulated by using mixture of Isopropyl myristate and oleic acid as oil phase, Tween-80 as surfactant, Isopropyl alcohol and Ethanol mixture as co-surfactant by phase titration method. The prepared formulations were evaluated for Limpidity (% transmittance), droplet size, Zeta potential, Electrical conductivity, Rheology, pH, percentage of drug (assay), emulsifying time, in vitro drug diffusion studies and ex vivo permeation studies. Results and conclusion: The Optimized micro emulsion (Micro emulsion 11) formulation containing Quetiapine fumarate (25mg), Surfactant mixture (50%w/w), Oil (12%w/w) and distilled water (38%w/w) has a droplet size of 26.70 nm with a zeta potential of -5.62 millivolts. The micro emulsion was characterized and compared with the pure drug suspension. Microemulsion showed 31.25 fold increased solubility than that of pure drug suspension. In vitro drug release and ex vivo permeation study results were comparable and correlative. The Microemulsion 11 formulation showed 1.4763 times more drug release than that of pure drug suspension. The formulation was found to be stable for three months. Keywords: Microemulsion, Phase titration method, Quetiapine Fumarate,Â  Emulsifying time.